Seasonal benthic species composition linked to coastal defense structures (CDS) in Kuala Nerus, Terengganu, Malaysia - Ibrahim, Nur Fazne; Abd Hamid, Muzzalifah; Mohd Akhir, Mohd Fadzil; Chuan Ong, Meng; Wan Talaat, Wan Izatul Asma; Idris, Izwandy (PeerJ, 2023)
Background The natural hydrodynamic process of Kuala Nerus, Terengganu, has changed since the extension of Sultan Mahmud Airport runway in 2008. Consequently, severe coastal erosion has occurred in the area, particularly during the northeast monsoon season (NEM). Numerous types of coastal defense structures (CDS) have been constructed to protect the coastline. Despite the loss of esthetic values, the effect of CDS construction on marine organisms in the area remains unknown. Hence, this study aims to assess the ecological aspects of macrobenthic compositions at the CDS area of Kuala Nerus, Terengganu, based on the differences between the southwest (SWM) and northeast (NEM) monsoon seasons. Methods Macrobenthos were collected from the sediment in July (SWM) and December 2021 (NEM) using the Ponar grab at 12 substations from five sampling stations. Results The density of macrobenthos was higher in SWM (48,190.82 ind./m2) than in NEM (24,504.83 ind./m2), with phylum Mollusca recording the highest species composition (60–99.3%). The macrobenthos species had a low to moderate level of diversity (H’ = 1.4–3.1) with the species were almost evenly distributed (J’ = 0.2–0.8). Windward substations exhibited coarser grain sizes (38.56%–86.84%), whereas landward substations exhibited very fine grain sizes (44.26%–86.70%). The SWM season recorded a higher organic matter content (1.6%–6.33%) than the NEM season (0.4%–3.1%). However, metal concentrations in the surface sediment were within the safe range and permissible limits for both seasons, inferring that the macrobenthos composition was unaffected. Discussion This study demonstrated that the CDS associated with the monsoon system has controlled the hydrodynamics and nearshore sedimentary processes in the Kuala Nerus coastal zone, thereby affecting the macrobenthos population, in terms of richness and density. The ecological and energetic effects of the coastal structures in different seasons have resulted in a more significant result, with the SWM exhibiting a higher macrobenthos composition than the NEM.
Keywords: Coastal defense structure; Kuala Nerus; Benthic ecosystem; Benthos; Breakwaters; Monsoon